Efficacy of 0.01% Atropine for Myopia Progression in Children Aged 5 Years to 16 Years - Yadav, Navin; Malik, Anu; Dr. R.C. Gupta,; Gupta, Alka; Singh, Lokesh Kumar; Jaishree Dwivedi, (Nepalese Journal of Ophthalmology, 2026)
Introduction: Myopia is an increasingly prevalent global public health concern, particularly among children, with potential long-term visual complications. Low-dose atropine has emerged as promising pharmacological intervention for controlling myopia progression. Objective: To evaluate the efficacy and safety of 0.01% atropine eye drops in controlling myopia progression in children over one year. Methodology: A placebo-controlled, interventional study was conducted for one year in ophthalmology department of a tertiary care centre. A total of 189 eyes (95 participants) were included in treatment group and 150 eyes (75 participants) in control group. Baseline and follow-up assessments at four, eight, and 12 months included axial length, spherical equivalent, distance uncorrected visual acuity, amplitude of accommodation, intraocular pressure, pupil diameter, and fundus examination. Statistical analysis was performed using Epi Info software, and a p-value <0.05 was considered statistically significant. Result: At 12 months, treatment group demonstrated significantly reduced myopia progression compared with control group. Mean spherical equivalent was 2.61 ± 0.30 dioptres in treatment group and 2.83 ± 0.36 dioptres in control group (p <0.001). True myopia progression was 0.53 ± 0.22 dioptres in treatment group compared with 0.84 ± 0.48 dioptres in control group (p <0.001). Axial length elongation was significantly lower in treatment group (0.19 ± 0.08 millimetres) compared with control group (0.36 ± 0.24 millimetres) (p <0.001). The control group demonstrated consistently poorer uncorrected visual acuity (p <0.001). Statistically significant differences were also observed in photopic pupil diameter and amplitude of accommodation (p <0.05). Intraocular pressure was slightly lower in treatment group but remained within physiological limits (p <0.05). Conclusion: Topical 0.01% atropine effectively reduced myopia progression and axial elongation in children over one year, with a favourable safety profile and minimal clinically significant effects on accommodation, intraocular pressure, and pupil diameter.